Estratégia de marcas próprias: estudo multicaso no atacado brasileiro - Piato, éderson Luiz (2006)
For the past years, wholesaling has been stimulated by a series of changes in its traditional activities. Through a deeper involvement with marketing strategies, wholesaling has included the management of own brands to its activities. However, academic literature s references include mostly inferences about own brands strategies in retailing. Therefore, wholesaling does not have the proper focus to evidence its involvement with own brands strategy. The purpose of this dissertation is to identify and analyze the marketing elements that influence the management of wholesaling own brands, and to evidence advantages and disadvantages that some of the most important Brazilian s wholesalers face when they decide to introduce own brands. First of all, a theory reference is developed, including some issues related to own brands, such as marketing strategies development, description of the main elements of marketing strategy and the development of own brands strategy. During the empirical research, a multi-case study with wholesalers and industries that supply own brands is developed. The aim of the interviews with the wholesalers is to identify the elements of marketing strategy that influence the management of own brands strategies. To do so, managers responsible for own brands in three Brazilian wholesalers are interviewed. The companies were chosen because they concentrate the higher level of own brands development in Brazilian wholesaling. The industries are interviewed to corroborate the process of own brands suppliers selection and evaluation. Managers of two industries, both of them responsible for the supplying agreements with wholesalers, were interviewed. These interviews focused only issues concerning the selection and evaluation process. As a result of the research, it is possible to identify the main elements of marketing that influence wholesalers own brands management, the advantages and disadvantages (or difficulties) of this strategy, as well as to understand the importance of suppliers selection and evaluation process for the effectiveness of own brands strategy. The information allowed the inference of some critical and fundamental elements for the management of own brands strategy in wholesaling. Besides that, the dissertation also contributes for the development of future researches that may consolidate the construction of a broader knowledge about own brands in wholesaling.